Great Enhancement in the Seebeck Coefficient and Thermoelectric Properties of Solid PEDOT:PSS Films Through Molecular Energy Filtering by Zwitterions - Chang'an Li; Dou Luo; Teng Wang; Chengwei Shan; Chen Li; Kuan Sun; Aung Ko Ko Kyaw; Jianyong Ouyang (Small Structures, 2023)
Organic thermoelectric (TE) materials are considered as the next‐generation TE materials owing to their merits including high mechanical flexibility, low cost, abundant elements, and nontoxicity. However, their Seebeck coefficient is lower than that of the inorganic counterparts by around one order of magnitude, and thus they have a lower dimensionless figure of merit (ZT) value. Herein, the significant enhancement in the Seebeck coefficient and thus the overall TE properties of poly(3,4‐ethylenedioxythiophene):poly(styrenesulfonate) (PEDOT:PSS) that is the most popular TE polymer by adding a zwitterion like rhodamine 101 (R101), N‐dodecyl‐N,N‐dimethyl‐3‐ammonio‐1‐propane‐sulfonate (DDMAP), or 1‐(N,N‐dimethylcarbamoyl)‐4‐(2‐sulfoethyl) pyridinium hydroxide (DMCSP) are reported. In particular, R101 can enhance the Seebeck coefficient of the acid‐then‐base‐treated PEDOT:PSS from 21.2 to 61.6 μV K−1. The PEDOT:PSS/R101 film can exhibit a power factor of 546 μW m−1 K−2 and a ZT of 0.46 that is the highest for pure organic solid films. The enhancement in the Seebeck coefficient is ascribed to the energy filtering induced by the dipole moment of zwitterion and the π–π overlapping between conjugated rhodamine 101 and PEDOT:PSS. To distinguish it from the conventional methods, this method is named as the molecular energy filtering.